1998
DOI: 10.1097/00004714-199808000-00009
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Haloperidol-Controlled Dose-Finding Study of Ziprasidone in Hospitalized Patients With Schizophrenia or Schizoaffective Disorder

Abstract: Ninety patients with schizophrenia or schizoaffective disorder according to DSM-III-R criteria participated in this double-blind, exploratory, dose-ranging trial. After a single-blind washout period of 4 to 7 days, patients were randomly assigned to receive one of four fixed doses of the new antipsychotic, ziprasidone 4 (N = 19), 10 (N = 17), 40 (N = 17), or 160 (N = 20) mg/day or haloperidol 15 mg/day (N = 17) for 4 weeks. A dose-response relationship among ziprasidone groups was established for improvements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
5

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(88 citation statements)
references
References 9 publications
7
75
0
5
Order By: Relevance
“…The incidence of extrapyramidal symptoms in the present study was much lower than that associated with conventional neuroleptic therapy in the literature (Ortiz and Gershon, 1986;Keepers et al 1983;Casey and Keepers 1988). This observation is consistent with the findings of another short-term study where ziprasidone in doses up to 160 mg/day were shown to have lower potential to induce movement disorders than haloperidol 15 mg/day (Goff et al 1998). Although there was evidence of a relationship between ziprasidone 160 mg/day and emergent EPS classified as an adverse event, this was very infrequent (7%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The incidence of extrapyramidal symptoms in the present study was much lower than that associated with conventional neuroleptic therapy in the literature (Ortiz and Gershon, 1986;Keepers et al 1983;Casey and Keepers 1988). This observation is consistent with the findings of another short-term study where ziprasidone in doses up to 160 mg/day were shown to have lower potential to induce movement disorders than haloperidol 15 mg/day (Goff et al 1998). Although there was evidence of a relationship between ziprasidone 160 mg/day and emergent EPS classified as an adverse event, this was very infrequent (7%).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, only one patient discontinued with movement disorders. Collectively, the investigations of motor side effects undertaken in this study are consistent with the very low propensity for movement disorders predicted by the in vitro receptor binding profile, PET studies, and the relatively low potency for induction of catalepsy (Seeger et al 1995) and observed in other clinical trials (Goff et al 1998, Keck et al 1998.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Seven RCTs were included in the original review: Arato 1997, 289 Brook 1998, 288 Daniel 1999, 290 Goff 1998, 291 Hirsch 1999, 292 , 293 Swift 1998. 294 Data extraction sheets for these studies can be found in appendix 3.…”
Section: Old Rctsmentioning
confidence: 99%
“…In human PET studies, 40 mg oral ziprasidone occupies B72% D 2 receptors using the D 2 antagonist radiotracer [ 11 C]raclopride (Bench et al, 1996) and B95% 5-HT 2A receptors using the 5-HT 2A antagonist radioligand [ 18 F]setoperone (Fischman et al, 1996) 4-8 h post-dose. In patients with acute exacerbations of schizophrenia and schizoaffective disorder, randomized double-blind studies have shown ziprasidone to have efficacy superior to placebo (Daniel et al, 1999;Keck et al, 1998) and similar to haloperidol (Goff et al, 1998). In stable patients, it reduces relapse rate compared to placebo (Arato et al, 2002) and appears to have higher efficacy against negative symptoms than haloperidol (Hirsch et al, 2002).…”
Section: Introductionmentioning
confidence: 99%